Identification of seaweed species from pasir putih beach, Tangerang Regency - Miftah Faridj; Lukman Anugrah Agung; Saifullah Saifullah (Jurnal Perikanan Terpadu, 2025)
Seaweed is one of the potential fisheries resources of Indonesia. The potency of seaweed can be developed due to its high economic value, abundance, and the potential use as a food and non-food products. The study aims to identify the types of seaweed found on the coast of Pasir Putih Beach and analyze its potential as a cultivation commodity. This research was conducted using the observation method and was carried out in April 2025 at Pasir Putih Beach, Tangerang Regency, Banten Province. Then identification was carried out at the Aquaculture Laboratory (BDP) of the Fisheries Science Study Program, Faculty of Agriculture, Sultan Ageng Tirtayasa University. Purposive Random Sampling method. Sampling was conducted at each sampling station. The results obtained were collected and presented in tabular format and then analyzed descriptively. Furthermore, the data were identified using the “algae base” database, seaweed identification book, and other related literature. The results found three species of macroalgae consisting of one type of green algae (Chlorophyceace), and two types of red algae (Rhodophyceae). The three seaweed species identified are Chaetomorpha crassa, Gracilaria coronopifolia, Acanthophora spicifera. Two out of three species found in Pasir Putih Beach, Tangerang Regency have the potential as an aquaculture commodity